Integration of Transcriptomics and Proteomics Improves the Characterization of the Role of Mussel Gills in a Bacterial Waterborne Infection - Saco, Amaro; Panebianco, Antonella; Blanco, Sofía; Novoa, Beatriz; Diz, Angel P.; Figueras, Antonio (Frontiers in Marine Science, 2021)
In recent years, the immune response of mussels (Mytilus galloprovincialis) has been studied at the transcriptomic level against several bacterial infections. As a result, different immune mechanisms have been revealed, including both conserved essential innate pathways and particularities of the mussel immune response according to its nature and environment. However, there is often a lack of functional verification because mussels are a non-model species and because transcriptomic and proteomic information is not always well correlated. In the current study, a high-throughput quantitative proteomics study coupled to LC-MS/MS analysis using isobaric tandem mass tags (TMTs) for protein labeling was employed to study the mussel gill immune response to a Vibrio splendidus bath (waterborne) infection at a functional protein level. A total of 4,242 proteins were identified and quantified, of which 226 were differentially expressed (DEPs) after infection, giving to the study a depth that was lacking in previous proteomic studies of the bivalve immune response. Modulated proteins evidenced an important cytoskeletal disruption caused by bacterial infection. A conserved network of associated proteins was modulated, regulating oxidative stress and NF-kB inflammatory responses and leading to innate immunity effectors. Proteomic results were submitted to an integrated analysis with those obtained in a previous transcriptomic approach with the same infection. Half of all the quantified proteins had a concordant transcriptomic expression trend, but this concordance increased when focusing on the DEPs. The correlation was higher within the immune-related DEPs, and the activation of the conserved NF-kB pro-inflammatory pathway was the main response in both approaches. The results of both techniques could be integrated to obtain a more complete vision of the response.